(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2013)
Background: Hypospadias is a common congenital anomaly of male urethra. Surgical repair is the only treatment of this defect, but there is no single, universally acceptable technique for its repair . Snodgrass technique is now popular for its low complication rate, shorter operative time, vertically oriented slit like meatus and better cosmetic outcome. Objective: To evaluate the role of vascularized dorsal dartos pedicle flap over the neourethra in terms of postoperative urethrocutaneous fistula formation between two groups of patients of distal penile hypospadias. Methodology: Thirty two patients were included in this study. They were divided in group A and group B on the basis of serial number of patients. Snodgrass urethroplasty was done in group A considered as control and in group B, Snodgrass urethroplasty was done with additional dorsal dartos flap by buttonhole technique considered as interventional group. The outcome of both groups in terms of post operative urethrocutaneous fistula were evaluated. Results: In this study in group A, urethrocutaneous fistula developed in 6 patients out of 16 patients. Among the fistulas, 5 were situated at the coronal level and 1 at the hypospadiac meatus level. In group B, urethrocutaneous fistula developed in 1 patient out of 16 patients and the fistula occurred at the coronal level. In either group, all the fistulas are developed after removal of the catheter. In terms of post operative urethrocutaneous fistula formation in between the two groups, the results were statistically significant. Conclusion: Snodgrass urethroplasty with additional dorsal dartos flap by buttonhole technique have better outcome than without additional dorsal dartos flap in terms of postoperative fistula formation. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15161 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 31-35